Effects of Surfactants on the Rate of Chemical Reactions - B. Samiey; C.-H. Cheng; J. Wu (Journal of Chemistry)
Surfactants are self-assembled compounds that depend on their structure and electric charge can interact as monomer or micelle with other compounds (substrates). These interactions which may catalyze or inhibit the reaction rates are studied with pseudophase, cooperativity, and stoichiometric (classical) models. In this review, we discuss applying these models to study surfactant-substrate interactions and their effects on Diels-Alder, redox, photochemical, decomposition, enzymatic, isomerization, ligand exchange, radical, and nucleophilic reactions.